2004
DOI: 10.1501/ashd_0000000052
|View full text |Cite
|
Sign up to set email alerts
|

Serum Malondialdehyde Levels and Superoxide Dismutase Activities in Pulmonary Tuberculosis and Lung Cancers

Abstract: Objectives: An increasing amount of epidemiological and experimental evidence has been carried out on the relationship between free radical activity and malignancy. The imbalance between free radical production and cellular defense mechanisms has been described in cancers and degenerative diseases like tuberculosis (tb).Methodology: The present investigation has been undertaken to study the levels of lipid peroxide (LP) and antioxidant enzyme superoxide dismutase (SOD) activities in sera of lung cancers (Lc) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
7
1
1
Order By: Relevance
“…The SOD activity in serum from patients with lung cancers was markedly lower than the TB patients and healthy control (p<0.001), activities of serum SOD in TB patients significantly decreased as compared to healthy controls (p<0.05) (Yıldız Güney, 2004). In the present study, we found that pleural SOD activity of TPE was higher than of MPE.…”
Section: Discussioncontrasting
confidence: 43%
“…The SOD activity in serum from patients with lung cancers was markedly lower than the TB patients and healthy control (p<0.001), activities of serum SOD in TB patients significantly decreased as compared to healthy controls (p<0.05) (Yıldız Güney, 2004). In the present study, we found that pleural SOD activity of TPE was higher than of MPE.…”
Section: Discussioncontrasting
confidence: 43%
“…Telomere is the structures of DNA proteins that do not contain genes (non-coding) which are located at the end of the chromosome and experience shortening with each cycle of cell division [11,16]. In this study, the average of telomere length was 584.59±305.92 bp.…”
Section: Telomere Lengthmentioning
confidence: 67%
“…However, this balance can shift when free radical production increases. Oxidative stress results from an imbalance between free radical production and a radical dampening system, either increasing free radical production or decreasing the antioxidant activity of defense or both [16]. [17].…”
Section: Telomere Lengthmentioning
confidence: 99%
“…37 In a previous study, serum SOD activities were significantly decreased in TB patients compared with healthy controls, and serum malondialdehyde (MDA) levels were increased. 38,39 This result indicates that OS is increased in patients with lung tuberculosis. Durak et al investigated pleural fluid and serum superoxide dismutase (SOD) values in patients with lung cancer, TB and heart failure, and found that pleural fluid and serum SOD values of all patient groups, being the highest in the TB group, were higher than the control group values.…”
Section: F I G U R E 3 Disulphide Levels Between Groupsmentioning
confidence: 86%